Job satisfaction and stress among healthcare workers in public hospitals in Qatar. Issue 1 (2nd January 2020) - Yehya, Arij; Sankaranarayanan, Anoop; Alkhal, Abdullatif; Alnoimi, Huda; Almeer, Nabila; Khan, Abdulwahid; Ghuloum, Suhaila
Abstract: This article explores predictors of job satisfaction and stress among clinicians and administrative staff at the public health sector in the State of Qatar. This is a rapidly growing sector, aiming for excellence in service, education and research. The vast majority of the staff are expatriates with different cultural backgrounds, and varying qualifications. After obtaining ethical approvals to conduct the study, the target population were asked to complete an anonymous online survey, that included sociodemographic data followed by the National Institute for Occupational Safety and Health (NIOSH) generic Job Stress questionnaire. Total number included in the analysis is 1260, female, married with children. Role ambiguity, conflict, skill underutilization and workload were associated with job dissatisfaction. Role and job future ambiguity were significantly associated with depression.